Effect of Sn addition on the microstructure and magnetic properties of FePt thin film - Chun, DongWon; Kim, SungMan; Kim, GyeungHo; Jeung, WonYoung (AMER INST PHYSICS, 2009)
An attempt has been made in this study to incorporate an alloying element to lower the order-disorder transformation temperature of Fe-Pt alloy and the effect of Sn addition was investigated for this purpose. The coercivity of the FePtSn film is measured to be about 5000 Oe, whereas that of FePt film is several hundred Oe at the annealing temperature of 300 C. Therefore, Sn addition is effective to promote the L1(0) ordering and reduce the ordering temperature of FePt alloy. Analysis of crystal structure by x-ray diffraction reveals that the lattice expansion of cubic FePt phase is induced by Sn addition in as-deposited film. After the annealing from 300 degrees C to 600 degrees C, L1(0) ordered phase is formed in FePtSn films and lattice constant of FePtSn film is approached to pure FePt with increasing annealing temperature up to 600 degrees C. Difference in solid solubility of Sn between disordered and ordered phase exists and thus excess Sn will diffuse out from ordered FePt L1(0) phase. Segregated Sn is found at the surface and interfacial region of the ordered FePtSn confirmed by depth profiling of Auger electron spectroscopy. The key role played by Sn addition in FePt alloy is therefore explained by reduction in activation energy for the L1(0) ordering-disordering transformation through high internal stress in disordered phase induced by supersaturated Sn atoms. (c) 2009 American Institute of Physics. [DOI: 10.1063/1.3075981]
Keywords: TEMPERATURE; CU